English Language Teacher Education and Subject Constitution: A State of the Art - Davila Rubio, Alejandro Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This literature review aims to present an analysis of the most recent developments in the study of English Language Teachers Educators’ (ELTEs) identity. In the first section, I present a profiling work aimed to identify main areas of research in Language Teacher Education, where identity emerges as an important concern for different scholars (Barkhuizen, 2017; Da Costa & Norton, 2017; Golombek & Klager, 2015; Norton, 2013). The analysis indicates that NEST/NNEST dichotomy, pre-service teachers, identity work, and critical theory appear as main trends in ELTE’s identity. Nevertheless, this literature review also attempts to make visible an area of research work that has not been widely explored in an explicit way namely the subject constitution of ELTEs.